Outer membrane vesicles as platform vaccine technology. Issue 11 (11th November 2015) - van der Pol, Leo; Stork, Michiel; van der Ley, Peter
Abstract: Outer membrane vesicles (OMVs) are released spontaneously during growth by many Gram‐negative bacteria. They present a range of surface antigens in a native conformation and have natural properties like immunogenicity, self‐adjuvation and uptake by immune cells which make them attractive for application as vaccines against pathogenic bacteria. In particular with Neisseria meningitidis, they have been investigated extensively and an OMV‐containing meningococcal vaccine has recently been approved by regulatory agencies. Genetic engineering of the OMV‐producing bacteria can be used to improve and expand their usefulness as vaccines. Recent work on meningitis B vaccines shows that OMVs can be modified, such as for lipopolysaccharide reactogenicity, to yield an OMV product that is safe and effective. The overexpression of crucial antigens or simultaneous expression of multiple antigenic variants as well as the expression of heterologous antigens enable expansion of their range of applications. In addition, modifications may increase the yield of OMV production and can be combined with specific production processes to obtain high amounts of well‐defined, stable and uniform OMV particle vaccine products. Further improvement can facilitate the development of OMVs as platform vaccine product for multiple applications. Abstract : Outer membrane vesicles (OMVs) are released spontaneously during growth by many Gram‐negative bacteria. They present a range of surface antigens in a native conformation and have natural properties like immunogenicity, self‐adjuvation and uptake by immune cells which make them attractive for application as vaccines against pathogenic bacteria. In particular with Neisseria meningitidis, they have been investigated extensively and an OMV‐containing meningococcal vaccine has recently been approved by regulatory agencies. Genetic engineering of the OMV‐producing bacteria can be used to improve and expand their usefulness as vaccines. Recent work on meningitis B vaccines shows that OMVs can be modified, such as for lipopolysaccharide reactogenicity, to yield an OMV product that is safe and effective. The overexpression of crucial antigens or simultaneous expression of multiple antigenic variants as well as the expression of heterologous antigens enable expansion of their range of applications. In addition, modifications may increase the yield of OMV production and can be combined with specific production processes to obtain high amounts of well‐defined, stable and uniform OMV particle vaccine products. Further improvement can facilitate the development of OMVs as platform vaccine product for multiple applications.